KAJIAN SIFAT KIMIA TANAH PADA LAHAN BERLERENG TANAMAN CENGKEH (Syzygium aromaticum L) DI SALURANG KECAMATAN TABUKAN SELATAN TENGAH - Sandil, Ayu Nathalia; Montolalu, Maria; Kawulusan, Rafli I. (Soil and Environment Journal, 2021)
STUDY ON SOIL CHEMICAL PROPERTIES ON SLOPING LAND OF CLOVE PLANTS (Syzygium aromaticum L.) IN SALURANG TABUKAN SELATAN TENGAH The aims of this study were: to determine soil pH, organic-C , nitrogen, phosphorus and potassium in clove plantations in Kampung Salurang, Tabukan Selatan Tengah. This research was conducted using a descriptive method as follows: disturbed soil samples were taken on a different position sloping area, namely upper slope (LA), middle slope (LT) and lower slope (LB). Each of them consists of 3 composite soil samples which taken from soil around clove plant. Parameters observed were soil chemical properties, namely soil pH, organic-C, total-N, available-P and available-K. The results showed that the characteristics of the chemical properties of soil namely pH was classified as neutral, organic-C was classified as low to moderate, total-N was classified as low, available-P was classified as moderate, and available-K was classified as very low.